Relationships between anxiety and depression in the workplace: epidemiological study among workers in a public university - Gavin, Rejane Salomão; Reisdorfer, Emilene; Zanetti, Ana Carolina Guidorizzi; Gherardi-Donato, Edilaine Cristina da Silva (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2017)
This study described the association between anxiety and depression and the relationship with sociodemographic factors among technical-administrative employees of a public university. Were interviewed 925 individuals, 54.7% female, with a mean age of 43.1 years. Logistic regression was performed seeking to evaluate the association between anxiety and depression through the stepwise forward method, with the independent variables entered from their p value in the bivariate analysis. The results confirmed the association between anxiety and depression, showing a probability of anxiety 4.40 times higher in people with depression. Was a predominance of females (54.9%), aged 40-49 years (38%) and that lives with a partner (66.4%).